A prata e outros metais em contextos funerários altimediévicos da Lusitania - Arezes, Andreia (2021)
Lusitania, the Roman province reorganized in the time of Augustus, covered a wide area of territory in the Iberian Peninsula. Despite the collapse of the political and administrative structures of the Roman Empire in the second half of the fifth century A.D., Lusitania maintained a set of characteristics that continued to enable its identification as heiress of romanitas. On the other hand, it became dominated by other powers, by new elites and their affirmation strategies: and in fact, in the sixth century, it was already integrated in the Visigothic kingdom formed in the meantime. In the background, Christianity: not univocal, but composed of several voices and, consequently, materialized in different ways. Funeral archaeology focused on these centuries reveals a multitude of options that challenge interpretation. Burial contexts where the deceased appear stripped of materials "coexist" with depositions associated with multiple types of artefacts. And if some of them are destined for the adornment of the bodies, what supposedly recalls pagan traditions others are imbued with a distinctive Christological dimension. Through the observation of different of LusitaniaŽs different funerary spaces with tombs attributed to the V-VI centuries, we propose to analyse the metallic materials channelled towards the tombs and to question the meaning inherent to their presence, underlining the contradictions or symbiosis they illustrate.